An analysis of the affordances for learning probability in a commonly used Mathematical Literacy textboo - Magwaza, Sthembile Lebohang (University of the Witwatersrand, Johannesburg, 2024)
The purpose of this study was to explore the examples that are used to present the topic of probability in a commonly used Mathematical Literacy textbook (Platinum Mathematical Literacy) in order to explore the affordances for learning for that are made available to users of this textbook. In this research report, I combine two frameworks, namely the framework for mathematics textbook analysis and the Variation Theory. The Dyadic framework for comprehensive textbook analysis is a result of a combination of the two frameworks. This framework was used to qualitatively analyse the chapter on probability in the Platinum Mathematical Literacy Grade 12 textbook, a textbook commonly used in many South African schools. The results of this study showed that the structure [general structure or example space] should be set out with the intention of exposing the critical features of the object of learning. The study further provided guidelines for textbook analysis to use to select a textbook that will afford learners optimum opportunities to learn.
A research report Submitted in fulfillment of the requirements for a Master of Education, In the Faculty of Humanities , Wits School of Education, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Mathematical Literacy; Variation Theory; Mathematics; Mathematics Education; Teaching; Learners; Textbook Analysis; Probability; SDG-4: Quality education